Estruturas de combustão identificadas no povoado pré-histórico de Leceia (Oeiras) - Cardoso, João Luis (2025)
All combustion structures identified in the prehistoric settlement of Leceia (Oeiras) are inventoried, distributed across a vast chronology corresponding to the Late Neolithic (ca. 3400-2900 BC), the Early Chalcolithic (ca. 2800-2500 BC) and the Full/Late Chalcolithic. (ca. 2500-2000 BC). The remarkable number of identified combustion structures, which reaches twenty-five, despite the general analogy between them, which is explained by the similarity of functions, allowed the identification of eight variants, duly characterized. This is the first contribution dedicated to the systematic study of combustion structures existing in a large prehistoric settlement in Portuguese territory.